A short-term durability comprehensive study of ceramic waste-doped White Cement composites with hooked-end, basalt and copper-coated fibers - Al-Sharhanee, Baraa Abduljabbar Badi; Mehmetoglu, Metin; Aygormez, Yurdakul; Nis, Anil (ELSEVIER, 2025)
White Cement (WC) mixes are an alternative product to the OPC. However, there are limited studies on the materials used in the production of composite materials as substitutes for the WC. Ceramic waste (CW) is an important alternative material in this regard. In this context, ceramic waste was replaced with White Cement at the rates of 5 %, 10 %, and 15 %, while three different fibers for reinforcement, namely hooked-end (HE) steel fiber, basalt (B) fiber, and copper-coated (CC) steel fiber (0.4 %) were used. The compressive and flexural strength results at 28 and 90 days were examined for the variations of White cement-based mortar properties. After 90 days, durability tests (sulfate effect, high temperature, and freeze-thaw) were applied while mechanical properties and weight losses were measured. SEM, XRD, Micro-CT, and TGA-DTA analyses were also used to see the changes with durability tests. According to the results, the increase in SiO2 and Al2O3 content in the addition of 5 % and 10 % ceramic waste increased the strength while keeping the pozzolanic reaction at a high level. In the case of 15 % substitution, it caused a reduction due to the decrease in the cement's relative content. The hooked-end steel fiber, which was denser and longer, had the highest performance, while the copper-coated steel fiber showed the lowest performance. With 5 % ceramic powder and hooked-end steel fiber reinforcement, the flexural strength was enhanced by 26 %, while the compressive strength was enhanced by 17 % compared to the 100 % White Cement sample (control sample).
Keywords: White cement; Ceramic waste; Fiber; Durability tests; FREEZE-THAW DURABILITY; SULFATE RESISTANCE; TEMPERATURE; CONCRETE; METAKAOLIN; STRENGTH; MORTARS; ATTACK; PERFORMANCE; CHLORIDE; Chemistry; Science & Technology - Other Topics; Environmental Sciences & Ecology